Perceptions of healthcare professionals and patients on the role of the pharmacist in TB management in Pakistan: A qualitative study - Atif, Muhammad; Munir, Kiran; Malik, Iram; Al-Worafi, Yaser Mohammed; Mushtaq, Irem; Ahmad, Nafees (Frontiers in Pharmacology, 2022)
Background: Globally, tuberculosis is the second major cause of death from infectious diseases worldwide; but particularly in developing countries. A multidisciplinary approach to the management of TB might go some way to help curb this disease. Objective: The objective of this study was to outline the perceptions of healthcare professionals and patients about the potential role of pharmacists in TB management in Pakistan. Method: This was a large qualitative study conducted at the Chest Disease Unit (CDU) of the Bahawal Victoria Hospital (BVH), Punjab, Pakistan. Data was collected from dialogue with physicians, pharmacists and patients through semi-structured interviews. There was a two stage recruitment process involving convenience and snowball sampling. Based on the objectives of the study, a pilot tested interview schema was developed, and used to conduct the interviews. The sample size was decided through standard saturation point criteria. All interviews were audio recorded and transcribed verbatim. The data was analyzed to draw conclusions using inductive thematic content analysis. Results: Analysis of the data yielded 22 categories and eight major themes which best explain the data. Physicians considered pharmacists as a qualified healthcare professional; whereas, patients considered them merely as a dispenser. Inventory management and dispensing of medicines were considered as major responsibilities of pharmacists. Physicians were extremely overburdened and wanted to share certain duties such as clinical monitoring and patient counseling with the pharmacists subject to their prior extensive trainings. However, they mentioned that diagnosis should only be done by the physicians. Most of the physicians were unaware of the legal scope of pharmacy practice in Pakistan. Improved patient care and sharing of burden of physicians were some of the proposed benefits of integrating pharmacists within TB management systems. Conclusion: This study set out to understand the role of the pharmacist in the tertiary care setting of a hospital in Bahawalpur, Pakistan. Healthcare professionals and patients viewed positively the role of pharmacists in TB management in Pakistan. However, healthcare policy makers should devise strategies to overcome the underlining barriers before assigning medicines-related clinical roles to pharmacists.